2005
DOI: 10.1111/j.1350-4126.2005.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

On the interpersonal regulation of emotions: Emotional reliance across gender, relationships, and cultures

Abstract: Three studies examine people's willingness to rely on others for emotional support. We propose that emotional reliance (ER) is typically beneficial to well-being. However, due to differing socialization and norms, ER is also expected to differ across gender and cultures. Further, following a self-determination theory perspective, we hypothesize that ER is facilitated by social partners who support one's psychological needs for autonomy, competence, and relatedness. Results from the studies supported the view t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
161
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(183 citation statements)
references
References 84 publications
8
161
1
7
Order By: Relevance
“…For example, the emotional autonomy scale (Steinberg & Silverberg, 1986), characterized by Ryan and Lynch (1989) as reflecting more detachment than autonomy, fell in the quadrant tapping pressured distance. In contrast, a scale of emotional reliance (Ryan, La Guardia, Solky-Butzel, Chirkov, & Kim, 2005), tapping adolescents' willing reliance on parents, fell in the volitional proximity-seeking quadrant. Van Petegem et al (2013) further showed that the dimension of distance (versus proximity) was positively related to both avoidance and anxiety-based forms of attachment, whereas the dimension of volition (versus pressure) was negatively related to these insecure attachment styles.…”
Section: Distinguishing Autonomy From Independencementioning
confidence: 85%
See 2 more Smart Citations
“…For example, the emotional autonomy scale (Steinberg & Silverberg, 1986), characterized by Ryan and Lynch (1989) as reflecting more detachment than autonomy, fell in the quadrant tapping pressured distance. In contrast, a scale of emotional reliance (Ryan, La Guardia, Solky-Butzel, Chirkov, & Kim, 2005), tapping adolescents' willing reliance on parents, fell in the volitional proximity-seeking quadrant. Van Petegem et al (2013) further showed that the dimension of distance (versus proximity) was positively related to both avoidance and anxiety-based forms of attachment, whereas the dimension of volition (versus pressure) was negatively related to these insecure attachment styles.…”
Section: Distinguishing Autonomy From Independencementioning
confidence: 85%
“…In a more recent study of adult attachments, autonomy support, and emotional reliance, Lynch (2013) collected daily data on autonomy support and security of attachment to predict patterns of emotional reliance-that is, the individual's willingness to turn to another person for emotional support (see Ryan et al, 2005). It has been assumed by attachment theorists that secure attachments would be associated with positive abilities to recruit support from others when distressed (e.g., Belsky, 2002).…”
Section: Attachment and Autonomy In Adolescence And Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research has identified cultural variations in educational practices and teachers' beliefs (TALIS 2009), as well as in many other psychological topics of interest for the AIED research community, such as decision making, reasoning, motivation, self-regulation, collaboration, competition, personal values, and various aspects of perception and interpretation (Henrich et al 2010a;Various authors 2010;Purdie and Hattie 1996;Lynch et al 2009;Ryan et al 2005;Hofstede 2008).…”
Section: Investigating the Socio-cultural Status Of Aied Researchmentioning
confidence: 99%
“…Les résultats de la présente étude vont dans le sens de la théorie de l'autodétermination de Ryan et Deci (2000;2001;Deci & Ryan, 1985;Ryan, La Guardia, Solky-Butzel, Chirkov & Kim, 2005). Selon ces auteurs, un contexte social soutenant les trois besoins psychologiques d'autonomie, de compétence et d'appartenance / implication dans la relation représente des conditions optimales favorisant le développement harmonieux de l'individu et la bonne santé mentale.…”
Section: Relation Entre Comportements Interpersonnels Et Dépressionunclassified